Caught in the Trap: Takotsubo Cardiomyopathy Masquerading as Acute Hypoxic Respiratory Failure" a case report - Muhammad, Bilal; Nguyen, Cindy; Arshad, Khurram; Latif, Rabia; Ali, Farman; Alamro, Yazan; Reddy, Siri Vallabah; Ahmad, Mohsin (Cardiology and Cardiovascular Medicine, 2024)
Takotsubo syndrome (TTS), also known as Gebrochenes-Herz syndrome or "octopus trap" by Japanese fishermen, is a reversible nonischemic cardiac pathology characterized by regional wall motion abnormalities visible on echocardiogram. While its etiology remains unknown, factors such as sudden catecholamine surges and emotional stress have been implicated. Here, we present a case of TTS in a 73-yearold female who presented with acute hypoxic respiratory failure requiring intubation. Initially suspected to be anaphylaxis or stroke, further evaluation revealed classic findings of TTS on transthoracic echocardiogram. Despite initial challenges in obtaining a detailed history due to intubation, the patient's recent severe emotional distress following the death of her pet cat emerged as a significant stressor. Management involved guidelinedirected medical therapy, and the patient was discharged to a rehab facility on the eighth post-admission day. This case underscores the importance of considering TTS in patients presenting with acute hypoxic respiratory failure, particularly in elderly females with recent stressful events, and highlights the need for prompt evaluation with point-of-care ultrasound to facilitate early diagnosis and appropriate management.